Anopheles funestus Populations across Africa Are Broadly Susceptible to Neonicotinoids but with Signals of Possible Cross-Resistance from the GSTe2 Gene - Tatiane Assatse; Magellan Tchouakui; Leon Mugenzi; Benjamin Menze; Daniel Nguiffo-Nguete; Williams Tchapga; Sevilor Kekeunou; Charles S. Wondji (Tropical Medicine and Infectious Disease, 2023)
Evaluating the susceptibility of malaria vectors to the new WHO-recommended products is a key step before large-scale deployment. We mapped the susceptibility profile of Anopheles funestus to neonicotinoids across Africa and established the diagnostic doses of acetamiprid and imidacloprid with acetone + MERO as solvent. Indoor resting An. funestus were collected in 2021 in Cameroon, Malawi, Ghana and Uganda. Susceptibility to clothianidin, imidacloprid and acetamiprid was evaluated using CDC bottle assays and offsprings of the field-caught adults. The L119F-GSTe2 marker was genotyped to assess the potential cross-resistance between clothianidin and this DDT/pyrethroid-resistant marker. Mosquitoes were susceptible to the three neonicotinoids diluted in acetone + MERO, whereas low mortality was noticed with ethanol or acetone alone. The doses of 6 µg/mL and 4 µg/mL were established as diagnostic concentrations of imidacloprid and acetamiprid, respectively, with acetone + MERO. Pre-exposure to synergists significantly restored the susceptibility to clothianidin. A positive correlation was observed between L119F-GSTe2 mutation and clothianidin resistance with the homozygote resistant mosquitoes being more able to survive than heterozygote or susceptible. This study revealed that An. funestus populations across Africa are susceptible to neonicotinoids, and as such, this insecticide class could be effectively implemented to control this species using IRS. However, potential cross-resistance conferred by GSTe2 calls for regular resistance monitoring in the field.